Antibacterial PLGA and PCL membranes, modified by magnetron sputtering method of copper target; IOP Conference Series: Materials Science and Engineering; Vol. 1093 : Advanced Materials for Engineering and Functional Purposes (AMEFP 2020) - Badaraev A. D. Arsalan Dorzhievich (2021, 2021)
Title screen